Reverse Engineering Nature to Design Biomimetic Total Knee Implants - Varadarajan, Kartik Mangudi; Zumbrunn, Thomas; Rubash, Harry E.; Malchau, Henrik; Muratoglu, Orhun K.; Li, Guoan (The Journal of Knee Surgery, 2015)
While contemporary total knee arthroplasty (TKA) provides tremendous clinical benefits, the normal feel and function of the knee is not fully restored. To address this, a novel design process was developed to reverse engineer “biomimetic” articular surfaces that are compatible with normal soft-tissue envelope and kinematics of the knee. The biomimetic articular surface is created by moving the TKA femoral component along in vivo kinematics of normal knees and carving out the tibial articular surface from a rectangular tibial block. Here, we describe the biomimetic design process. In addition, we utilize geometric comparisons and kinematic simulations to show that; (1) tibial articular surfaces of conventional implants are fundamentally incompatible with normal knee motion, and (2) the anatomic geometry of the biomimetic surface contributes directly to restoration of normal knee kinematics. Such biomimetic implants may enable us to achieve the long sought after goal of a “normal” knee post-TKA surgery.
Keywords: total knee arthroplasty; implant design; biomimetic implant; knee kinematics; normal knee